A method for stabilizing continuous-time switched linear systems. (August 2019) - Pérez, C.; Benítez, F.; García-Gutiérrez, J.B.
Abstract: This paper studies the stabilization of continuous-time switched linear systems in which the only control action is the switching law. We first present necessary and sufficient conditions for the stabilization of a continuous-time switched linear system. Based on this result, we deduce a method for defining the stabilizing switching law. Moreover, this method is applied to the planar case and it is proved that the stabilizing switching law coincide to the results known in this case. Finally, in order to illustrate the results and apply the method, several numerical examples are presented.